Bowel Obstruction due to Migration of an Intragastric Balloon Necessitating Surgical Removal before Completion of the Recommended 6 Months - Seyed Morteza Mousavi Naeini; Mahdi Sheikh (Case Reports in Medicine)
We report a 25-year-old man with small bowel obstruction due to migration of a saline-filled intragastric balloon before the completion of the recommended 6 months of treatment who presented to the emergency department with abdominal pain. The patient had received a gastric balloon insertion 5 months prior. Within 24 hours of the original procedure, he noticed urine staining. The results of an endoscopy conducted the next day were normal. After ruling out other possible complications using endoscopy and confirming the diagnosis by computed tomography (CT) scan and conservative treatment for 48 hours the patient underwent surgery and the balloon was extracted. Due to the growing prevalence of obesity and the modalities used for treating it, physicians should be familiar with the side effects of each option and their presenting symptoms as well as the differential diagnosis they should not miss. Physicians must also improve their knowledge of how to approach these patients to avoid life-threatening complications caused by these modalities.